Incidence of Legionella and heterotrophic bacteria in household rainwater tanks in Azumino, Nagano prefecture, Japan. (January 2014) - Kobayashi, Michiko; Oana, Kozue; Kawakami, Yoshiyuki
ABSTRACT Many administrative agencies in Japan are encouraging installation of household rainwater‐storage tanks for more effective use of natural rainwater. Water samples were collected periodically from 43 rainwater tanks from 40 households and tested for the presence of Legionella species and the extent of heterotrophic bacteria in Azumino city, Nagano prefecture, Japan. PCR assays indicated the presence of Legionella spp. in 12 (30%) of the 43 tank water samples. Attempts were made to identify correlations between PCR positive samples, topography, pH, chemical oxygen demand (COD), atmospheric temperature and the numbers of heterotrophic bacteria. Between June and October, 2012, the numbers of heterotrophic bacteria in rainwater tanks and the values of COD positively correlated with the presence of Legionella species. In most of the Legionella‐positive cases, heterotrophic bacterial cell counts were >104 CFU/mL. Moreover, Legionella species were less frequently detected when the COD value was >5 mg KMnO4/L. Therefore, at least in Azumino, Japan between June and October 2012, both heterotrophic bacterial counts and COD values may be considered index parameters for the presence of Legionella cells in rainwater tanks. Much more accumulation of such data is needed to verify the accuracy of these findings.